MEMBANGUN STRATEGI PENDIDIKAN BERBASIS PARADIGMA PEMBELAJARAN - Luh Kompiang Sari (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
Along with the development of the globalization era in the field of education, there has been a change in the educational paradigm, namely the shift of the teaching paradigm towards the learning paradigm, which will give more roles to students (student center). This movement makes a reform in developing good learning strategies to respond to challenges in the future. Learning strategies are the science and art of managing learning to get results in achieving goals through and together with others in the context of planning, mobilizing and evaluating. Effective learning strategies include general principles and the methods chosen to deliver material in a particular learning environment. For this reason, it is important to design learning strategies that are able to create an atmosphere and learning process that is fun, stimulating, and challenges students to build their potential and develop creativity optimally in accordance with their talents and abilities.Keywords: Strategy, Paradigm, Learning